The Effectiveness of Learning to Produce Exposition Texts with Project Based Models in Vocational High Schools, Based on Specialization Department (Universitas Negeri Semarang, 2018)
Curriculum 2013 explains the increase in student competency in the affective, social skills and skill thinking is the main goal of learning. Curriculum 2013 explains the increase in student competency in the affective, social skills and skill thinking is the main goal of learning. The purpose of this study was to analyze the effectiveness of learning to produce exposition texts with project-based models in Vocational High Schools based on specialization department. The research method uses an experimental method with design pre-post test control group. The research method used an experimental method with a control group pre-post test design. The technique of collecting data uses tests, questionnaires, and documentation. The data analysis technique uses descriptive statistics and inferential statistics with an average difference test and Anova. The results of this study are project-based models that effectively improve the skills of producing text exposition of Vocational High School students, who has a special interest in light vehicle engineering. The results of these study benefit students, teachers, and schools in improving the quality of learning in Bahasa Indonesia. For students, this study is to improve mastery of learning material and improve the ability to produce text. For teachers, it can provide broad insight into the project-based learning model. For schools, it can use as a reference in making policies about improving the quality of learning in schools. (tvalue = 10.464 p < 0.01).